Bibliometric Analysis of Global Research on Clavulanic Acid - Howard Ramirez-Malule (MDPI AG, 2018)
Clavulanic acid (CA), a potent inhibitor of the β-lactam, ase enzyme, is frequently co-formulated with a broad spectrum of antibiotics to treat infections caused by β-lactamase-producing pathogens. In order to evaluate the impact and the progress of CA studies in the last four decades, a bibliometric analysis of the global scientific production of CA was carried out. A total of 39,758 records in the field of CA were indexed in the Scopus database for a 43-year period of study (1975⁻2017). The results indicated that CA studies have grown, showing three phases (1975⁻1999, 2000⁻2003 and 2004⁻2017) based on records of publications; the results showed a sigmoidal profile. Medicine was the main subject area for CA studies, whereas biochemistry, genetics and molecular biology were areas of research for CA production by Streptomyces clavuligerus (S. clavuligerus). Nevertheless, chemical engineering (as a subject area) had the highest increase in the percentage of publications related to CA production by S. clavuligerus. The United States, France, the United Kingdom, Spain and Brazil were the leading countries in the scientific production of studies on both CA and CA related to S. clavuligerus. This analysis allowed the identification of the area of knowledge with the highest impact on CA studies, the top researchers and their geographic distribution, and also helped to highlight the existence of antibiotic-resistant bacteria as an emergent area in CA research.